STYLISTIC MEANS OF ACHIEVING LEXICAL ECONOMY IN ENGLISH AND UZBEK TEXTS: A COMPARATIVE STUDY - Omonov Baxtiyor (TADQIQOTLAR, 2026)
Abstract This article examines the stylistic means through which lexical economy is achieved in English and Uzbek texts. Lexical economy is understood as the linguistic tendency to express complex meanings using minimal lexical and structural resources. The study analyzes stylistic devices such as ellipsis, abbreviation, metaphor, lexical substitution, word-formation processes, agglutinative morphology, idiomatic expressions, and contextual omission. A qualitative descriptive and comparative methodology is employed, based on data drawn from literary works, journalistic discourse, everyday communication, and digital media in both languages. The findings demonstrate that English primarily achieves lexical economy through syntactic compression, abbreviation, and metaphorical expression, whereas Uzbek relies mainly on agglutinative morphology, contextual inference, and idiomatic units. Despite typological differences, both languages reveal a shared communicative principle of efficiency and expressiveness. The study highlights implications for translation, language teaching, and cross-linguistic communication.